Anti-infective vaccination in the 21st century — new horizons for personal and public health. (October 2015) - Scully, Ingrid L; Swanson, Kena; Green, Luke; Jansen, Kathrin U; Anderson, Annaliesa S
Highlights: Vaccines preserve public health through infectious disease prevention. Declining rates of vaccination imperil public health. Breakthrough vaccines this century have targeted devastating invasive diseases. New vaccines are in development to protect unborn and newborn infants through maternal immunization. After 100 years of vaccine development focused on protecting entire populations, new vaccines are being targeted at groups of individuals specifically at risk of infection. Although many advances have been made in the field of vaccines, challenges remain for targets such as HIV and Chlamydia trachomatis . Abstract : The 21st century has seen the licensure of new anti-infective vaccines that have demonstrated their benefit for both individual and population (herd) protection. Despite this there are still many human pathogens for which no vaccine is available. As we learn more about these pathogens, and as technologies advance, more opportunities for vaccine development have become available. This review will address these advances and highlight the paradigm shift from vaccines that are used on a population basis, to others which will have an individual benefit, if successfully licensed, but are not expected to have widespread population based use. The development of the latter vaccines has resulted in a paradigm shift toward vaccinating individuals at specific risk for infection from bacteria such as Staphylococcus aureus or Clostridium difficile, which are members of normal human flora but can cause severe disease under certain circumstances. Increasing levels of antibiotic resistance in such bacteria such as S. aureus have also driven the urgency for the identification of alternative methods of protection that do not rely on treatment or prophylaxis with antibiotics.